Harnessing anti-parity-time phase transition in coupled topological photonic valley waveguides - Xie, Xinrong (2023)
Topological and non-Hermitian physics provide powerful tools for manipulating light in different ways. Recently, intense studies have converged on the interplay between topology and non-Hermiticity, and have produced fruitful results in various photonic settings. Currently, the realization of this interplay falls under the paradigm of enabling energy exchange between topological systems and the environment. Beyond this paradigm, it is revealed that a non-Hermitian phenomenon, i.e., the anti-parity-time phase transition, naturally emerges from a Hermitian system realized by coupled topological valley waveguides. Such phase transition gives two exotic topological superstates in the spectral domain. By further combining the two phases with topological robustness, a photonic topological bi-functional device is realized on a silicon-on-insulator platform at telecommunications frequencies. The results provide a new perspective on light manipulation and integrated device applications.